KEARIFAN LOKAL DALAM PEMBANGUNAN HUKUM MEWUJUDKAN GOOD GOVERMENT - Winarno, Ronny (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
The law reflects the culture of society. Every society always produces culture, so the law always exists in society and appears with its distinctiveness. Community culture is part of local wisdom that reflects character, noble values, rules, order as a reflection of living law, hereditary has & been recognized by the wider community. Its perspective, concept and simplicity can be a source of law to realize good governance. Legal development, not only preparing normative or regulatory aspects, but also the role of legal development in realizing good governance. The results showed that in some regions there are still commendable actions such as corruption, hampering the good governance process.